A Catalog of Stellar and Dust Properties for 500,000 Stars in the Southwest Bar of the Small Magellanic Cloud - Petia Yanchulova Merica-Jones; Karl Gordon; Karin Sandstrom; Claire E. Murray; L. Clifton Johnson; Julianne J. Dalcanton; Julia Roman-Duval; Jeremy Chastenet; Benjamin F. Williams; Daniel R. Weisz; Andrew E. Dolphin (The Astrophysical Journal)
We present a catalog of individual stellar and dust extinction properties along close to 500,000 sight lines in the southwest bar of the Small Magellanic Cloud (SMC). The catalog is based on multiband Hubble Space Telescope photometric data spanning near-ultraviolet to near-infrared wavelengths from the Small Magellanic Cloud Investigation of Dust and Gas Evolution survey (SMIDGE) covering a 100 × 200 pc area. We use the probabilistic technique of the Bayesian Extinction And Stellar Tool (BEAST) to model the spectral energy distributions of individual stars in SMIDGE and include the effects of observational uncertainties in the data. We compare BEAST-derived dust extinction properties with tracers of the interstellar medium, such as the emission from the ^12 CO (2–1) transition ( I (CO)), the dust mass surface density (Σ _dust ) from far-IR emission, the H i column density ( N (H i )) from the 21 cm transition, and the mass fraction of polycyclic aromatic hydrocarbons (PAHs; q _PAH , derived from IR emission). We find that the dust extinction ( A ( V )) in the SMIDGE field is strongly correlated with Σ _dust and I (CO), and less so with N (H i ) and q _PAH , and suggest potential explanations. Our extinction measurements are also sensitive to the presence of the 2175 Å bump in the extinction curve toward UV bright stars. While most do not show evidence for the bump, we identify ∼200 lines of sight that are 2175 Å bump candidates. Furthermore, we find distinct structures in the dust extinction–distance distributions that provide insights into the 3D geometry of the SMC.